STUDIES ON EXPERIMENTAL HYPERTENSION : XIX. THE PRODUCTION OF PERSISTENT HYPERTENSION IN SHEEP AND GOATS - Goldblatt, Harry (The Rockefeller University Press, 1943)
Persistent hypertension has been produced in the goat and sheep by constriction of the main renal arteries. The presence or absence of accompanying uremia depends upon the degree of constriction of the renal arteries. In both sheep and goat, constriction of one main renal artery also caused elevation of the blood pressure which tended to persist longer than in the dog. Excision of the one kidney with main renal artery constricted resulted in a prompt (24 hours) return of the blood pressure to normal. In the animals with hypertension of long duration but without renal excretory insufficiency, (the "benign" phase) no significant arterio- or arteriolosclerosis developed as a result of the hypertension alone. In the animals that had both hypertension and renal excretory insufficiency, (the "malignant" phase) the typical terminal arteriolar lesions developed in many organs. These lesions consisted of necrosis and fibrinoid degeneration of arterioles and necrotizing arteriolitis which should not be confused with arteriolosclerosis. The same humoral mechanism which is responsible for experimental renal hypertension in the dog and other animals also obtains in the pathogenesis of experimental renal hypertension in the sheep and goat.